Asymptotic properties of Lp-estimators - Ivanov, A.V. (Інститут математики НАН України, 2008)
Some sufficient conditions for consistency and asymptotic normality of a non-linear regression parameter Lp-estimator are presented for a continuous time regression model with Gaussian stationary noise possessing the long-range dependence or weak dependence property.